Menthacarin for long-term treatment of functional dyspepsia – Results from a clinical trial follow-up - Storr, Martin; Stracke, Berenike (Zeitschrift für Gastroenterologie, 2022)
Background Menthacarin was shown to be effective and safe in clinical trials in patients with functional dyspepsia (FD). Long-term treatment results have not been reported yet.Methods An open-label, 11-month follow-up (FU) was offered to FD patients who had undergone treatment with Menthacarin (1 gastro-resistant capsule b.i.d. vs. placebo (PL)) in a 4-week, double-blind, clinical trial. During FU, all patients (former verum and PL) were treated with 1 gastro-resistant capsule Menthacarin b.i.d. Main outcomes were the changes in pain intensity and severity of sensation of pressure, heaviness, and fullness from original baseline and global improvement.Results 70 patients were included in the analyses (former Menthacarin group: 36, former PL group: 34). At the end of the PL-controlled study phase, all 3 main efficacy variables were statistically significantly improved in the Menthacarin group compared to PL. In the FU phase, former PL patients started to improve under Menthacarin treatment towards the outcomes seen in the former Menthacarin group (alignment at approximately 6 months), while former Menthacarin patients showed sustained or even continuously improved outcomes by month 12. At study end, more than 90% of patients were “much or very much improved" in both groups. Menthacarin treatment was well tolerated.Conclusions The favorable effects seen in the FU period suggest that Menthacarin is a valuable treatment option in FD patients who require symptomatic treatment also in the longer term for up to 12 months.
Keywords: Funktionelle Dyspepsie; Follow-up-Studie; Kümmelöl; Pfefferminzöl; Menthacarin